Effects of the Activator and Twin Block on Facial Soft Tissue Thickness in Class II Division 1 Patients - Mehmet Akın; Ömer Polat; Zehra İleri; Faruk Ayhan Başçiftçi (Galenos Yayinevi, 2014)
Objective:The purpose of this study was to evaluate and compare the effects of the activator and Twin Block appliances on soft tissue thickness in Class II division 1 patients.Materials and Methods:Soft tissue thickness measurements were obtained from standardized lateral and posteroanterior cephalograms taken at the beginning and end of the time the appliances were used. The study patients consisted of 3 different groups: the control group (group I) comprised 30 patients (13 male, 17 female; mean age: 12.15 6 0.61 years); the activator group (group II) comprised 30 patients (12 male, 18 female; mean age: 12.15 6 0.68 years); and the Twin Block group (group III) comprised 30 patients (14 male, 16 female; mean age: 12.10 6 0.62 years). In the present study, 12 linear anthropologic points were measured. Intragroup comparisons were analyzed using the paired samples t test; and for the intergroup comparisons, the ANOVA and Tukey tests were used at the p , 0.05 level.Results:According to the intragroup comparisons, there were significant differences in groups II and III in the skeletal measurements (SNB, ANB, L1-NB, UL-E plane, and LL-E plane), and in the soft tissue thickness measurements (labrale superius, stomion, labiomental, pogonion, and gnathion) (p,0.05). When the treatment changes were compared between the groups, there were no significant differences between groups II and III. However, between groups I and II or III there were significant differences in the measurements of the SNB, ANB, L1-NB, UL-E plane, LL-E plane, and labiomental soft tissue thicknesses.Conclusions:Both the activator and Twin Block therapies improved the mandibular advancement in Class II patients and affected the soft tissue thickness in a similar way; only the labiomental region was affected.